Analisis Tingkat Pemahaman Siswa Pada Interaksi Sosial Multikultural - agus tohawi (Institut Agama Islam Pangeran Diponegoro Nganjuk, 2024)
This paper describes the social interaction in educational institutions whose learning citizens are multicultural. Students' understanding of multicultural values ​​will shape different social behavior at the level of understanding and social action. This research was carried out at SMPN 1 Kertosono, which since the establishment of the school was formed from multicultural learning residents. The focus of the research in this article is to describe: a) the expression of student identity in multicultural differences, b) the contribution of subject teachers to the level of understanding of multicultural interactions. This study uses a qualitative method. Furthermore, as a theoretical foundation in qualitative research, it is fundamentally based on phenomenology. Meanwhile, in this study using the type of grounded theory research. This type of research is based on data and facts found in the field, so it is not based on pre-determined ideas. The results of the research, a) the implications of student expression tend to mean mutual tolerance for differences in social, ethnic and religious status, b) role models and the application of multicultural values ​​by all subject teachers is a real form of understanding multicultural values ​​that must be preserved in the educational environment